2014
DOI: 10.2323/jgam.60.198
|View full text |Cite
|
Sign up to set email alerts
|

Direct fermentation of amorphous cellulose to ethanol by engineered Saccharomyces cerevisiae coexpressing Trichoderma viride EG3 and BGL1

Abstract: Direct ethanol fermentation from amorphous cellulose was achieved using an engineered industrial Saccharomyces cerevisiae strain. Two cellulase genes endoglucanase (eg3) and β-glucosidase (bgl1) were obtained from Trichoderma viride and integrated into the genome of S. cerevisiae. These two cellulases could be constitutively coexpressed and secreted by the recombinant strain S. cerevisiae-eb. The enzyme activities were analyzed in the culture supernatants, with the highest endoglucanase activity of 2.34 units/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…The current study indicated that the final ethanol concentration reached 7.53 g/L, and the conversion rates of ethanol were 0.377 g/g glucose and 0.151 g/g dry orange peel. These indices approached or exceeded those previously reported ( Yamada et al, 2013 ; Gong et al, 2014 ; Yu and Li, 2015 ; Wu et al, 2018 ).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The current study indicated that the final ethanol concentration reached 7.53 g/L, and the conversion rates of ethanol were 0.377 g/g glucose and 0.151 g/g dry orange peel. These indices approached or exceeded those previously reported ( Yamada et al, 2013 ; Gong et al, 2014 ; Yu and Li, 2015 ; Wu et al, 2018 ).…”
Section: Discussionsupporting
confidence: 81%
“…The construction of cellulase gene-engineered S. cerevisiae was an effective approach to achieve in situ saccharification and ethanol production. S. cerevisiae coexpressing cellulase/cellodextrin and Trichoderma viride EG3/BGL1 produced ethanol contents of 4.3 g/L ( Yamada et al, 2013 ) and 4.63 g/L ( Gong et al, 2014 ). S. cerevisiae expressing Aspergillus aculeatus β-glucosidase achieved an ethanol content of 15 g/L ( Treebupachatsakul et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, cellulolytic enzyme yield was significantly improved for a non-fermentation fungus Neurospora crassa by genetic engineering [ 17 , 18 ]. Saccharomyces cerevisiae was enabled to utilize cellulose by integration of endoglucanase and β-glucosidase genes from Tichoderma viride [ 19 ]. S .…”
Section: Introductionmentioning
confidence: 99%
“…A similar work published before by Voorend et al [53] suggested that the overexpression of GA20-OXIDASE1 in maize increased the saccharification of modified biomass after NaOH pretreatment [53]. Therefore, apart from developing pretreatment technologies and composing enzyme consortiums, lignocellulose feedstock improvement also seems to be a feasible strategy to enhance bioethanol yields [54][55][56][57][58].…”
Section: Bioethanol Production Using Molecular Tools and Genetically Modified Organismsmentioning
confidence: 91%